Designing a marketing knowledge policy package in free trade zones based on the tacit knowledge of experts using (research example: arvand free trade zone) - Ehsan Abaspoor; Ibrahim Albonaimi; Haghighi Mohammad (مدیریت راهبردی دانش سازمانی)
The creation of a free trade zone plays an important role in the circulation of exports, economic growth and employment, but financial, managerial and economic reasons have caused that there has been no serious movement to achieve the goals and some of the desired goals have not been realized. This research has been done with the aim of designing a policy package of marketing knowledge in free trade zones based on the tacit knowledge of experts using metacombination method. This research is qualitative and inductive in nature with a survey strategy that uses the interview technique. In the meta-composition method, the books, documents and research articles of the investigated community, which entered the meta-composition process after several stages of screening, 21 components were identified as the most important codes that played an essential role in the creation of marketing policies of free trade zones. A policy package that includes the main (mother) policies and supporting policies in three categories of barriers, enablers and facilitators has been presented. The marketing programs of the free trade zones are made through increasing the integrations according to the parent policies and supporting policies